Decreasing water resources in Southeastern U.S. as observed by the GRACE satellites - Johanna Engström (IWA Publishing, 2021)
Changing water quantities and location can be estimated using the Gravity Recovery and Climate Experiment (GRACE) satellites. By measuring differences in the Earth's gravity, the satellites provide monthly data on regional changes in the Earth's mass resulting from the movement of water. Studying the Southeast U.S., using the full record of the original GRACE satellites (2002–2016), a significant trend of declining water quantities appears in west-central Alabama, extending into eastern Mississippi. These findings confirm earlier research which indicates declining streamflow levels but develops this research further by estimating the amount lost as 11.6 km3. Considering the different terrestrial water storages by analyzing data from the National Climate Assessment – Land Data Assimilation System Noah 3.3 Version 2 (NCA-LDAS) indicates that the majority of this loss can be attributed to groundwater losses, a finding that is further confirmed by well records throughout the region. HIGHLIGHTS An area of decreasing water resources is found in Alabama-Mississippi.; Irrigation using groundwater has increased during the study period.; Losses identified are tied to declining groundwater levels in the region.;